PERFORMANCE MANAGEMENT OF PEKANBARU ENVIRONMENT AND FORESTRY EDUCATION AND TRAINING CENTER (BDLHK) - Dian Maya Sari; Dadang Mashur (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
The Environmental and Forestry Education and Training Center (BDLHK) Pekanbaru as a technical implementing unit has the task and function of providing forestry education and training. In carrying out its duties and functions, BDLHK Pekanbaru still experiencing several forest problems in its working area, education and training has not become an employee career system, the results of the Identification of Training Needs (IKD) have not been able to provide accurate information and the capacity of widyaiswara to carry out teaching activities at certain trainings especially in terms of dealing with the latest issues is still limited. The purpose of this research was to analyze the performance management of BDLHK Pekanbaru and to find out the inhibiting factors. This research uses the performance management theory proposed by Edward Deming which consists of planning, implementation/action, and reviewing. This research uses a qualitative research type with a descriptive approach. The results of this research indicate that the Performance Management of BDLHK Pekanbaru is not running optimally, this can be seen in terms of planning, implementation and monitoring. The obstacles by BDLHK Pekanbaru are the limited capacity of education and training management personnel, adaptation of new patterns in the implementation of education and training also budget recofusing.